Rural agriculture teachers’ comprehension and implementation of self-regulation - McKendree, Robert B. (Kansas State University, 2015)
This qualitative study investigated four rural Kansas high school agriculture teachers’ comprehension and implementation of self-regulation strategies in their own professional growth and in their instructional practice. Each participant was interviewed three times, using symbolic interactionism as the methodological framework and the Seidman technique of interviewing. The participants included two males and two females, each one having between five and 20 years of teaching experience. Three questions guided this study: (1) how do rural Kansas high school agriculture teachers make meaning of self-regulation and the processes needed to facilitate self-regulation, (2) in what ways do teachers self-regulate for their own professional growth purposes, and (3) what strategies do teachers use to foster self-regulation in their students? Findings suggest while participants described utilizing strategies that are associated with self-regulated learning, they have an incomplete understanding of self-regulated learning and they most closely associated it with effort and motivation. The perceived incomplete understanding may be attributable in part to a lack of formal training in metacognitive processes. Nevertheless, when participants perceived value in professional development, they described consciously using self-regulated learning strategies such as seeking assistance, self-evaluation, and self-monitoring, which all indicate participants utilize components of self-regulation to grow professionally. However, even though participants described utilizing all three phases of self-regulation processes to affect growth in their own careers, there was a disconnect when participants described how they try to facilitate these processes within their students. Participants often described attempting to foster growth in self-regulation among students by targeting motivation-oriented behaviors, instead of targeting the underlying cognitive ability to utilize self-regulation processes. Implications for practice are presented, including the possible need for further education concerning self-regulated learning in order to produce pedagogical content knowledge in self-regulation processes. Instruction connecting the three phases of the self-regulation model could assist agricultural educators with forming a more complete understanding of self-regulated learning. Recommendations for future research are discussed including investigating effective teaching strategies for delivering self-regulation instruction to teachers, as well as investigating the possible impact self-regulation instruction has on various attributes of teachers and students, such as self-efficacy and career orientation.
Keywords: Metacognition; Self-regulation; Agricultural education; Education, Agricultural (0517)